The Decision Support System for Selecting Village Head Candidates Using The AHP Method Is Implemented With Super Decision Software: Sistem Pendukung Keputusan Pemilihan Calon Kepala Desa Menggunakan Metode AHP Diimplementasikan Dengan Software Super Decision - Yanti Yusman; Ranti Eka Putri; Loli Amelia (SYSTEMATICS, 2022)
Indonesia is a democratic country which has elections general according to which level with this genera election provide sustainability in development in an area but not in five klambir this study aims to analyze the use of the AHP method to determine the decision in the election of a candidate for village head in klambir five which is part of Deli Serdang Regency, Medan City in The election the village head has inequakity in the election of village heads, this is very important it is very felt that this research uses the AHP method in analyzing data descriptive, qualitative, by collecting data by conducting interviews directly to the community in the election of candidates for village heads with assistance the five in klambir community provide an overview as well provide convenience in research in determining or selecting candidates village head.